The relationship between complexity behavior and enterprise growth: A case of savings and credit cooperatives in Uganda - Michael Omeke; Pascal T. Ngoboka; Isaac Nabeta Nkote; Isaac Kayongo (Cogent Business & Management, 2019)
This study examines the relationship between complexity behavior and enterprise growth in savings and credit cooperatives (SACCOs) in Uganda. A cross-sectional survey was conducted in the four regions of Uganda, using a mixed method approach. Primary data was collected using a self-administered questionnaire from 269 SACCOs in Uganda. Zero-order correlation, regression analysis, and structural equation modeling techniques were used to analyze the data. The study findings indicate a positive and significant relationship between complexity behavior and enterprise growth in SACCOs in Uganda. Furthermore, the dimensions of complexity behavior (self-organizing, adaptive behavior, and networking) are found to be positively and significantly correlated with enterprise growth in SACCOs in Uganda. This research focuses on the role of complexity behavior in promoting enterprise growth in a developing economy.
Keywords: 650; enterprise growth; complexity behavior; adaptive behavior; self-organizing; and networking